Infraorbital Myofibroma of Infra-orbital Region: A Rare Case Report - Wirya N. Sabr; Marwan N. Hassan; Yadgar A. Saeed; Hardi M. Dhahir; Aso S. Muhialdeen; Zanyar A. Mohammed; Fahmi H. Kakamad; Abdulwahid M. Salih; Zana B. Najmadden; Shko H. Hassan (Barw Medical Journal, 2023)
AbstractIntroductionInfantile myofibroma is a rare tumor of myofibroblastic origin that can affect soft tissue, bones, or internal organs. The aim of the current study is to report a rare case of a solitary infra-orbital infantile myofibroma.Case presentationAn 11-month-girl presented with progressive swelling of the left infra-ocular region for two weeks. On examination, there was a well-defined swelling with a localized border that was firm, non-mobile, tender, fixed to the underlying bone, and non-adherent to the superficial skin. Under general anesthesia, the right infraorbital mass was excised. The wound was closed by layers, and the histopathological examination revealed a 3 cm myofibroblastic mass that invaded the margins at multiple spots.ConclusionInfraorbital myofibroma is an extremely rare type of myofibroma. Excision with primary closure is the definitive management therapy.